The buffalo robe - Baxter, Linda; Kabel, Larassa (Logan, IA : Perfection Learning Corp., 1998)
As Three Willows spoke, she rose. She brought a bundle to the tiny fire. She untied the straps that held it. Then she unrolled the buffalo robe. It was large, soft and carefully tanned. Red Fox peered through the dim light of the tipi. He could see colorful drawings painted on the smooth side of the robe. Red Fox reached out to touch one scene. It was a man on horseback. He was racing across the prairie. Red Fox could almost feel the movement of the horse under the rider as they raced. "That's your father," whispered Three Willows.
Keywords: Teton Indians -- Juvenile fiction; Teton Indians -- Fiction; Indians of North America -- Fiction